Protected areas and their surrounding territory: socioecological systems in the context of ecological solidarity. Issue 1 (8th February 2016) - Mathevet, Raphaël; Thompson, John D.; Folke, Carl; Chapin, F. Stuart
Abstract: The concept of ecological solidarity (ES) is a major feature of the 2006 law reforming national park policy in France. In the context of biodiversity conservation, the objectives of this study are to outline the historical development of ES, provide a working definition, and present a method for its implementation that combines environmental pragmatism and adaptive management. First, we highlight how ES provides a focus on the interdependencies among humans and nonhuman components of the socioecological system. In doing so, we identify ES within a framework that distinguishes ecological, socioecological, and sociopolitical interdependencies. In making such interdependencies apparent to humans who are not aware of their existence, the concept of ES promotes collective action as an alternative or complementary approach to state‐ or market‐based approaches. By focusing on the awareness, feelings, and acknowledgement of interdependencies between actors and between humans and nonhumans, we present and discuss a learning‐based approach (participatory modeling) that allows stakeholders to work together to construct cultural landscapes for present and future generations. Using two case studies, we show how an ES analysis goes beyond the ecosystem management approach to take into account how human interactions with the environment embody cultural, social, and economic values and endorse an ethically integrated science of care and responsibility. ES recognizes the diversity of these values as a practical foundation for socially engaged and accountable actions. Finally, we discuss how ES enhances academic support for a socioecological systems approach to biodiversity conservation and promotes collaboration with decision‐makers and stakeholders involved in the adaptive management of protected areas and their surrounding landscapes.